(untitled) (World Economics and Finance Bulletin, 2025)
This study aims to show the role of integrated reporting in enhancing the cultural dimensions within the commercial banks listed in the Iraq Stock Exchange, and to analyze the extent to which this role is reflected on the value of the economic unit . The interest in this topic came in light of the increasing importance of comprehensive disclosure, which is not limited to financial information, but also includes non-financial capital, which is a key pillar in building the bank’s identity and enhancing the confidence of its customers